Inflammatory and Metabolic Responses to Different Resistance Training on Chronic Obstructive Pulmonary Disease: A Randomized Control Trial - Silva, Bruna S. de Alencar; Lira, Fábio S.; Rossi, Fabrício E.; Ramos, Dionei; Uzeloto, Juliana S.; Freire, Ana P. C. F.; Lima, Fabiano F. de; Gobbo, Luís A.; Ramos, Ercy M. C. (Frontiers in Physiology, 2018)
Background: Low-grade inflammation can be present in chronic obstructive pulmonary disease (COPD), which may affect the regulation of muscle protein and body metabolism. Regular practice of exercises show improvement in muscle strength and dyspnea in patients with COPD, however, the response to training on inflammatory and metabolic disorders is unclear. In this study, we compared the effects of resistance training using weight machines and elastic resistance (bands and tubes) on the inflammatory and metabolic responses in individuals with COPD. Methods: Patients with COPD were randomized into three groups: elastic band group (EBG), elastic tube group (ETG), and weight machines equipment group (MG). EBG and ETG were analyzed together (elastic group (EG)). The participants were evaluated for pulmonary function (spirometry), peripheral muscle strength (digital dynamometry), IL-6, TNF-α, IL-10, IL-15 (Immunoassay), glucose, triacylglycerol, total cholesterol, HDL-c, and albumin levels (Enzymatic colorimetric). Blood samples were collected to assess the acute and chronic exercise responses after 12 weeks of training protocol. Results: The patients’s mean age was 71.53 ± 6.97 years old. FEV1 (percent predicted) was 50.69±16.67% and 45.40±15.15% for EG and MG, respectively (p=0.28). All groups increased muscle strength (p<0.05) with no differences between groups. The acute response to exercise after 12 weeks of training showed an improve on inflammation behavior when compared to baseline. Regarding the chronic effects, it was observed a decrease of all cytokines, except IL-10 (p<0.05). After 12 weeks of training, the analysis of the metabolic profile presented a reduction in glucose concentration (p<0.01), with no differences between groups (p=0.30) and a decrease in triacylglycerol for the EG (p>0.01). Conclusions: Training with elastic resistances or conventional weight machines showed an improve on inflammation response after 12 weeks of training. Chronically, both training groups showed anti-inflammatory effects, with the EG showing a strong tendency to improve IL-10/TNF-α ratio and IL-10 levels. Trial registration: RBR-6V9SJJ.